Interdisciplinarity: A Critical Assessment - Jacobs, Jerry A.; Frickel, Scott (SSRN eLibrary, 2009)
This article draws together disparate research and theorizing on interdisciplinarity. We first describe widespread efforts to promote interdisciplinarity in U.S. universities and critically examine the assumptions underlying these initiatives. Next, we present a cross-sectional view of interdisciplinary communication, knowledge diffusion, research assessment, and interdisciplinary research centers. We then describe research and theories that provide historical perspectives on the disciplinary system, interdiscipline formation, applied and professional fields, and institutional fragmentation. We present original findings on the prevalence of research centers, faculty hiring patterns in hybrid fields, and the diffusion of research across disciplines in the humanities and social sciences. The review concludes with a critical summary and suggestions for future research.